Pemanfaatan Ruang Baca Jurusan Sejarah bagi Mahasiswa Jurusan Sejarah Fakultas Ilmu Sosial Universitas Negeri Padang - Erlangga, Rafi; Zafri, Zafri (TSAQOFAH, 2025)
This research is motivated by the low utilization of the History Department's reading room by History Department students at Universitas Negeri Padang. This reading room is a learning facility aimed at supporting the academic process within the history department. This study aims to determine the benefits of the History Department's reading room for History Department students at Universitas Negeri Padang. This research is a descriptive qualitative study. The subjects of this study were obtained through interviews with history students from the 2015, 2016, and 2017 cohorts at Universitas Negeri Padang. The data analysis technique used was interactive analysis, consisting of data collection, data reduction, data display, and data verification. The research findings indicate that, out of the 45 students who participated in this study, many reported numerous benefits of using the History Department's reading room, such as facilitating the completion of assignments and increasing class participation due to frequent reading and borrowing books from the reading room. However, some students did not utilize the reading room due to reasons such as an incomplete book collection, inadequate facilities, particularly the air conditioning, and unfriendly library staff.